PENGEMBANGAN E-MODUL UNSUR MAKRONUTRIEN DAN MIKRONUTRIEN DALAM AIR LAUT PADA MATA KULIAH KIMIA KELAUTAN MENGGUNAKAN APLIKASI CANVA - Setyadilla, Rahmah; Alwi, Wiwit; Nurhamidah, Nurhamidah (University of Bengkulu, 2024)
This research and development aims to (1) produce an E-Module designed with the Canva Application (2) determine the feasibility and response of students to the E-Module being developed. The resulting product is an E-Module which contains on macronutrient and micronutrient elements in sea water. The development model used is the Borg and Gall development model which has been modified by Sugiyono. This development has 10 stages, but in this case the development is limited to stage 7, namely product revision I. The development stages carried out in this research are potential and problems, data collection, product design, design validation, design revision, product testing, and product revision I. This research and development was carried out at Bengkulu University from March to September 2023. The test subjects in this research were students of Chemistry Education Study Program who were taking Marine Chemistry classes for the 2022/2023 academic year and 2023/2024 academic year at Bengkulu University Teacher Training and Education Faculty, totalling 25 people. Data collection was carried out using student needs questionnaires, literature studies, atudent respon questionnaires and product validation sheets. The data obtained are qualitative data in the form of comments and suggestion from validators and respondents, quantitative data in the form of assessment numbers based on a Likert Skala. Quantitative data processing by analyzing product feasibility and analyzing student responses to the E-Module being developed. The result of the media and material validity test respectively were 98,61% and 88,88%. The Student response test result of 84,33%. Based on the results, it was concluded that the E-Module developed was very suitable to use in the classes.